Performance of the 2017 European Alliance of Associations for Rheumatology/American College of Rheumatology Classification Criteria in Patients With Idiopathic Inflammatory Myopathy and Anti–Melanoma Differentiation–Associated Protein 5 Positivity. Issue 9 (26th July 2022) - So, Ho; So, Jacqueline; Lam, Tommy Tsz‐On; Wong, Victor Tak‐Lung; Ho, Roy; Li, Wai Ling; Mok, Chi Chiu; Lau, Chak Sing; Tam, Lai‐Shan
Abstract : Objective: This study aimed to evaluate whether the 2017 European Alliance of Associations for Rheumatology (EULAR)/American College of Rheumatology (ACR) classification criteria for adult and juvenile idiopathic inflammatory myopathies (IIMs) could appropriately classify the diagnosis in adult patients with anti–melanoma differentiation–associated protein 5 (anti–MDA‐5)–positive IIM. In addition, this study sought to determine whether a status of anti–MDA‐5 positivity could be incorporated into the EULAR/ACR IIM classification criteria set and whether the recently modified criteria based on the presence of myositis‐specific autoantibodies (MSAs) could be used to appropriately classify the diagnosis in patients with anti–MDA‐5–positive IIM. Methods: Consecutive adult patients clinically diagnosed as having anti–MDA‐5–positive IIM from 10 hospitals in Hong Kong were retrospectively recruited; patient characteristics were obtained from electronic medical records. We used a commercial line blot immunoassay to detect MSAs. We also determined a proposed set of phenotypic‐serologic classification criteria specific for anti–MDA‐5. Results: In the patient cohort (n = 120; 31.7% with dermatomyositis, 68.3% with clinically amyopathic dermatomyositis [CADM]), the diagnosis could be classified with the EULAR/ACR criteria in 86 patients (71.7%) and with the Bohan and Peter criteria in 49 patients (40.8%). However, when combined with criteria specifically modified for CADM, the diagnosis could be classified by the Bohan and Peter criteria in 76.7% of patients. We observed that the sensitivity of the EULAR/ACR criteria could be improved to 98.3% if anti–MDA‐5 antibody–positive status was considered as one of the criteria. The MSA‐based criteria had 100% sensitivity. When we applied our proposed specific phenotypic‐serologic criteria for the classification of patients with anti–MDA‐5 antibodies, 97.5% of patients were able to be classified as having IIM. Conclusion: In this cohort of patients with anti–MDA‐5–positive IIM, the diagnosis could not be classified by the EULAR/ACR criteria in almost 30% of patients. We suggest incorporating anti–MDA‐5 antibody positivity as a criterion into existing criteria sets or developing specific criteria for patients with anti–MDA‐5–positive IIM.